2006
DOI: 10.1200/jco.2005.04.0824
|View full text |Cite
|
Sign up to set email alerts
|

Descriptive and Prognostic Value of Patient-Reported Outcomes: The Bortezomib Experience in Relapsed and Refractory Multiple Myeloma

Abstract: This study demonstrated the complementary value for PRO assessments in further interpreting clinical response, the impact of adverse effects, and patient prognosis in clinical trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
70
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(74 citation statements)
references
References 18 publications
3
70
0
1
Order By: Relevance
“…Rather, it is fully in line with the already consolidated evidence found in a number of other cancer populations [19]. Several studies have in fact shown that self-reported QoL frequently replaces important clinical data, such as performance status or tumor size, in final multivariate prognostic models [20,21].…”
Section: Editorialsupporting
confidence: 78%
“…Rather, it is fully in line with the already consolidated evidence found in a number of other cancer populations [19]. Several studies have in fact shown that self-reported QoL frequently replaces important clinical data, such as performance status or tumor size, in final multivariate prognostic models [20,21].…”
Section: Editorialsupporting
confidence: 78%
“…In research, anchor-based methods can be used to interpret mean differences or report the percentage of patients reporting clinically significant change or impairment. 8,[16][17][18] Distribution-based methods interpret results in terms of magnitude of mean difference and variability in a sample of subjects, such as effect size. Distribution-based methods can easily be applied to any continuous measure in a sample reporting means and standard deviations (SDs) or standard errors, although the results in a given sample cannot be applied to a new sample.…”
Section: Examination Of Clinical Significancementioning
confidence: 99%
“…Distribution-based methods can easily be applied to any continuous measure in a sample reporting means and standard deviations (SDs) or standard errors, although the results in a given sample cannot be applied to a new sample. This method is widely used in research [18][19][20] but is not suited to clinical applications.…”
Section: Examination Of Clinical Significancementioning
confidence: 99%
“…The aim of the medical treatment is not only prolongation of life, but also the preservation of its quality [1]. Simultaneously, a link has been observed between curation, or response in palliative treatment, and quality of life (QoL) [2]. Therefore a good balance between response and toxicity has to be found.…”
mentioning
confidence: 99%